'I wanted to safeguard the baby': a qualitative study to understand the experiences of Option B+ for pregnant women and the potential implications for 'test-and-treat' in four sub-Saharan African settings. (23rd July 2017) - McLean, Estelle; Renju, Jenny; Wamoyi, Joyce; Bukenya, Dominic; Ddaaki, William; Church, Kathryn; Zaba, Basia; Wringe, Alison
Abstract : Objective: To explore what influences on engagement with Option B+ in four sub-Saharan African settings. Methods: In-depth interviews were conducted in 2015, with 22 HIV-positive women who had been pregnant since Option B+ was available, and 15 healthcare workers (HCWs) involved in HIV service delivery. Participants were purposely selected from four health and demographic surveillance sites in Malawi, Tanzania and Uganda. A thematic content analysis was conducted to investigate what influenced engagement with Option B+. Results: Feeling 'ready' was key to pregnant women accepting antiretroviral treatment (ART) on the same day as diagnosis at antenatal clinic; this was influenced by previous knowledge of HIV-positive status, interactions with HCWs and relationship with their partners. The desire to protect their unborn infant was the main issue that motivated women to initiate treatment, temporarily over-riding barriers to starting ART. Many HCWs recognised that pressurising women into starting ART may lead them to stop treatment following delivery. However, their own responsibility to protect the infant sometimes drove HCWs to use strong persuasive techniques to initiate pregnant women onto ART as early as possible, occasionally causing women to disengage. Conclusions: Protecting the baby superseded feelings of unpreparedness for lifelong ART and may explain poor retention observed in Option B+ programmes. Women may benefit from more time to accept their status, and counselling on the long-term value of ART beyond the pregnancy and breastfeeding period. Strategies to promote readiness for same-day initiation of lifelong treatment are urgently needed, and may provide important lessons for universal test-and-treat implementation.